Measuring organised crime-related harms: exploring five policing methods - Tusikov, Natasha (Crime, law and social change, 2012)
Many law enforcement agencies around the world have adopted risk assessment methodologies to analyse organised crime. These assessments, which are intended to provide law enforcement management with rigourous analysis to enable rational and objective decision-making processes, are an integral part of intelligence-led policing. Despite the prevalence of these assessments, as the assessments and their methodologies are often tightly restricted within the law enforcement community, it is often unclear how law enforcement defines, analyses and makes decisions about organised crime. While the use of risk assessment methodology in policing to analyse organised crime is generally under-evaluated, critics point to serious methodological weaknesses. Another less-explored aspect in the scholarly literature is how law enforcement conceptualises and measures the impact of "harm" from organised crime and uses this analysis to inform priority-setting processes. This article explores how law enforcement assesses organised crime-related harm by examining five policing methods—one each from Australia and the Netherlands and three from the United Kingdom. The article finds that the methods have significant shortcomings: the main concepts are generally ill-defined and the operationalisation of these concepts is problematic. More importantly, the problems evident in the harm methods raise several critical questions, specifically whether measuring organised crime-related harms is empirically feasible and, if so, can be undertaken in a manner that meaningfully informs law enforcement’s decision-making and limits undue political interference.